Parameter Identification Algorithm for a Two Coherent-Area Reduced-Order Model Power System - Chavez-Orostica, H; Riquelme-Vera, E (Institute of Electrical and Electronics Engineers Inc., 2024)
With the increasing integration of sustainable energies and their power electronics interfaces, power systems have experienced a significant reduction in inertia, which can potentially lead to instability. Such disturbances can cause power systems to experience transient non-coherency, behaving as multiple independent electrical islands, where the synchronous generators within each zone oscillate coherently in frequency. Although detailed models are essential for implementing predictive and corrective methods, they present high complexity due to their large number of nonlinear equations. Consequently, there is a need for simplified models that accurately represent the behavior of multi-area power systems. In this study, an innovative algorithm is presented to identify the parameters of a reduced-order model that represents the frequency response of a two-area power system. The model and the algorithm are validated using simulated data from IEEE 39-Bus benchmark, and the results demonstrate the effectiveness of the algorithm in identifying system behavior. © 2024 IEEE.